Dry reforming of methane over Ni/dendritic fibrous SBA-15 (Ni/DFSBA-15): Optimization, mechanism, and regeneration studies - Chong, C.C. (Elsevier Ltd, 2020)
Dendritic fibrous type SBA-15 (DFSBA-15) was recently discovered with its outstanding catalytic performance and coke resistance as compared to the conventional SBA-15. The operating conditions for dry reforming of methane (DRM) over 10Ni/DFSAB-15 were optimized by using response surface methodology (RSM), followed by stability and regeneration study. Characterization results (TEM and FESEM) confirmed the homogenous distribution of NiO particles with no morphological change in spherical DFSBA-15 upon Ni addition. Process parameters, such as reaction temperature (X1, 700 Â°Câ900 Â°C), gas hourly space velocity (X2, 15,000 mL/g.h â 35,000 mL/g.h), and CH4/CO2 ratio (X3, 1â3) were studied over CO2 conversion (Y1), CH4 conversion (Y2), and H2/CO ratio (Y3). The optimal reaction conditions were found at X1 = 794.37 Â°C, X2 = 23,815.022 mL/g.h, and X3 = 1.199, with Y1 = 95.67, Y2 = 93.48, and Y3 = 0.983. The in-situ FTIR studies of adsorbed CH4, CO2, and CH4 + CO2 confirmed the formation of unidentate carbonate, bidentate carbonate, and linear carbonyl species as intermediate species. 10Ni/DFSBA-15 presented good reproducibility by using both regeneration medium (air and CO2/N2) with two-fold regeneration by air as compared to CO2/N2. It was proven that the synthesized 10Ni/DFSBA-15 was appreciably stable and prone to be regenerated by air for DRM under optimal conditions. Â© 2020 Hydrogen Energy Publications LLC